Manfaat Pengaruh Penggunaan Laba Dan Arus Kas Untuk Memprediksi Financial Distress - Bagas Hanindyo S; Arum Kusumaningdyah (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2019)
The purpose of the research is to find out empirically about the influence of earnings before tax and cash flows from operating activities of companies on the conditions of financial distress in manufacturing companies listed on the Indonesia Stock Exchange 2013-2016. The measurement of financial distress in this study is proxied to be two, namely earning before tax and cash flow from operating activities. The sample in this study is 144 of the 560 manufacturing company data listed on the Indonesia Stock Exchange 2013-2016. The data used in this study are secondary data derived from annual reports and sustainability reports of company. The results of this study indicate that earnings before tax have a positive and significant effect on detecting corporate financial distress While the cash flow from operating activities has a significant negative effect to detect financial distress conditions